Polyester resin containing photoreactive dopamine as well as preparation method and application of polyester resin
By integrating dopamine methacrylamide (DMA) into the PPF crosslinking network structure, a polyester resin containing photoreactive dopamine is formed, which solves the problem of hydrophobicity of the PPF material surface, significantly improves the hydrophilicity of the material, is suitable for 3D printing technology, and promotes the personalized manufacturing and bone regeneration of bone tissue engineering scaffolds.
Patent Information
- Application Number
- CN202510063607.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-15
AI Technical Summary
In the prior art, the surface hydrophobicity of PPF materials limits its application in bone tissue engineering, and it is difficult to meet the demand of 3D printing technology for the hydrophilicity of materials.
By integrating dopamine methacrylamide (DMA) into the PPF crosslinking network structure, a polyester resin containing photoreactive dopamine is formed, which significantly improves the hydrophilicity of the material surface.
The hydrophilicity of the polyester resin is significantly improved and is suitable for 3D printing technology, especially PμSL technology, and can manufacture high-precision personalized bone tissue engineering scaffolds and promote bone regeneration.
Smart Images

Figure CN119875027A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biomaterials, and in particular relates to a polyester resin containing photoreactive dopamine, and a preparation method and application thereof. Background Art
[0002] Bone tissue is an important dynamic and regenerative system in the human body, with a complex multi-level porous structure and excellent mechanical properties. Many patients who suffer from accidental trauma, bone tumors or spinal injuries face bone defects, which not only affect their mobility but may also threaten their health. To solve this problem, bone tissue engineering came into being. As an innovative treatment strategy, it combines the principles of life sciences and engineering, and provides a potential solution by developing biological substitutes that can repair, maintain or promote the restoration of function and morphology of human tissues and organs.
[0003] Bone tissue engineering scaffolds are alternative implants made of bioactive and biocompatible materials that can provide support for bone regeneration and simulate the extracellular matrix environment. The design and material selection of the scaffold are crucial. It must not only meet the mechanical performance requirements, but also have good biodegradability and biocompatibility. Among the many polymer biomaterials, photo-crosslinkable poly(propylene fumarate) (PPF) has become a material of great concern in bone tissue engineering due to its excellent biocompatibility, injectability and biodegradability. PPF can be degraded into fumaric acid and propylene glycol in the body and excreted from the body through normal metabolism. It is a very promising bone tissue engineering material.
[0004] With the continuous development of 3D printing technology, especially in the field of tissue engineering, this technology can be used to accurately design and manufacture complex three-dimensional bionic structures. Projection micro-stereolithography (PμSL), as a light-curing 3D printing technology, has become an ideal choice for manufacturing personalized bone tissue engineering scaffolds because of its ability to process complex micron-level structures with high resolution and high precision, and its strong cross-scale processing capabilities. In PμSL technology, the selection of surface hydrophilic materials is crucial to promoting cell growth. The hydrophilicity of the material surface can effectively improve the contact between the scaffold and body fluids, reduce protein adsorption, and thus improve the biocompatibility and tissue integration ability of the material. However, in the 3D printing application of PPF materials in the existing technology, the hydrophobicity of the PPF material surface limits its application in bone tissue engineering. Therefore, it is necessary to develop a new PPF material suitable for 3D printing. Summary of the invention
[0005] The present invention aims to solve at least one of the above-mentioned technical problems existing in the prior art. To this end, the present invention provides a polyester resin containing photoreactive dopamine, which integrates dopamine molecules into the PPF cross-linked network structure through dopaminemethacrylamide (DMA), and the hydrophilicity of the material surface is significantly improved, which is suitable for 3D printing, especially PμSL technology.
[0006] The invention also provides a method for preparing the polyester resin containing photoreactive dopamine.
[0007] The present invention also provides a biomedical material prepared from the polyester resin of the present invention.
[0008] The present invention also provides application of polyester resin in 3D printing.
[0009] A first aspect of the present invention provides a polyester resin containing photoreactive dopamine, wherein the raw materials for preparing the polyester resin include DMA, PPF, diethyl fumarate (DEF) and a photoinitiator.
[0010] The technical solution of the polyester resin containing photoreactive dopamine in the present invention has at least the following beneficial effects:
[0011] For cross-linked PPF scaffolds, one limitation of their application is the hydrophobicity of their surface. Therefore, surface modification of PPF scaffolds can make up for the limitation caused by the hydrophobicity of PPF surface. Polydopamine formed by self-polymerization of dopamine under alkaline and oxygen-containing conditions can provide good hydrophilicity for implants through the active functional groups contained in its structure. Dopamine has good biological activity and can be used as a modifier. Both dopamine monomer and polydopamine can promote the proliferation and mineralization of osteoblasts and induce osteogenic differentiation by adsorbing extracellular matrix and related proteins. In addition, due to the coordination ability of the catechol group in the dopamine molecule, it has excellent adhesion properties and can further produce strong interactions with many bioactive substances such as bone morphogenetic protein-2 (BMP-2). Various dopamine derivatives are also used as surface modification molecules of materials in bone tissue engineering, including DMA.
[0012] The invention provides a polyester resin containing photoreactive dopamine, and the dopamine molecules are integrated into the PPF cross-linked network structure through DMA, so that the hydrophilicity of the material surface is significantly improved.
[0013] The unsaturated polyester resin provided by the present invention can be applied to 3D printing technology based on PμSL, has a simple curing molding process, is not restricted in three-dimensional structure, has a wide range of applications, and the final molded product can be used to further load bioactive substances, and has broad application prospects in bone tissue engineering.
[0014] According to some embodiments of the present invention, the preparation raw materials include, by weight:
[0015] DMA: 5-15 parts,
[0016] PPF: 42.5~47.5 parts,
[0017] DEF: 42.5~47.5 parts,
[0018] Photoinitiator: 0.45 to 3.3 parts.
[0019] According to some embodiments of the present invention, the number average molecular weight of the PPF is 2489 and the weight average molecular weight is 5014.
[0020] According to some embodiments of the present invention, in preparing the raw material, PPF is dissolved in an equal mass of DEF.
[0021] The purpose of dissolving PPF in an equal mass of DEF is to reduce the viscosity of the resin so that it can maintain good fluidity during the 3D printing process. DEF, as a reactive diluent, can participate in the photocross-linking reaction of the polymer and accordingly retain the original mechanical properties of the polymer.
[0022] According to some embodiments of the present invention, the mass fraction of the photoinitiator in the total mass of DMA, PPF and DEF is preferably 0.5-3%.
[0023] According to some embodiments of the present invention, the mass fraction of the photoinitiator in the total mass of DMA, PPF and DEF is more preferably 1-2%.
[0024] According to some embodiments of the present invention, the synthesis method of DMA comprises the following steps: dissolving sodium tetraborate, sodium bicarbonate and dopamine hydrochloride in water, adjusting the pH of the system, then adding methacrylic anhydride dropwise, washing, extracting, drying and recrystallizing the product.
[0025] According to some embodiments of the present invention, sodium tetraborate, sodium bicarbonate and dopamine hydrochloride are dissolved in water, and the pH of the system is adjusted to be above 8.
[0026] According to some embodiments of the present invention, during the synthesis of DMA, the product is washed and extracted with ethyl acetate, then dried with anhydrous sodium sulfate, and finally the product is recrystallized in hexane to obtain a gray DMA solid.
[0027] According to some embodiments of the present invention, during the synthesis of DMA, the molar ratio of dopamine hydrochloride to methacrylic anhydride is preferably 1:1.1 to 1.12.
[0028] According to some embodiments of the present invention, during the synthesis of DMA, the reaction conditions are preferably to react overnight at room temperature under the protection of a nitrogen or argon atmosphere.
[0029] According to some embodiments of the present invention, the synthesis method of PPF comprises the following steps: mixing DEF, 1,2-propylene glycol, a catalyst and an inhibitor, performing a first step reaction to obtain a di(hydroxypropyl) fumarate intermediate, and then performing a second step ester exchange reaction to obtain the PPF after polycondensation.
[0030] According to some embodiments of the present invention, in the method for synthesizing PPF, the molar ratio of DEF, 1,2-propylene glycol, catalyst and inhibitor is preferably 1:2.8-3.5:0.008-0.02:0.002-0.003.
[0031] According to some embodiments of the present invention, in the method for synthesizing PPF, the molar ratio of DEF, 1,2-propylene glycol, catalyst and inhibitor is more preferably 1:2.9-3.2:0.009-0.015:0.002-0.003.
[0032] According to some embodiments of the present invention, the catalyst is preferably at least one of anhydrous zinc chloride and anhydrous aluminum chloride.
[0033] According to some embodiments of the present invention, the catalyst is more preferably anhydrous zinc chloride.
[0034] According to some embodiments of the present invention, the polymerization inhibitor is preferably at least one of hydroquinone (hydroquinone), p-benzoquinone, and methylhydroquinone.
[0035] According to some embodiments of the present invention, the polymerization inhibitor is more preferably hydroquinone.
[0036] According to some embodiments of the present invention, in the synthesis method of PPF, the conditions of the first step reaction are preferably stirring the reaction at 90-110° C. for 0.5-1 h under an inert gas atmosphere, and then heating to 140-150° C. for 6-8 h.
[0037] The conditions of the second step reaction are preferably under vacuum conditions (less than 1 mmHg) at 90-100° C. for 0.5-1 h, and then heated to 130-150° C. for 3-5 h until the desired molecular weight is obtained.
[0038] According to some embodiments of the present invention, the photoinitiator is preferably at least one of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide (i.e., photoinitiator 819), (2,4,6-trimethylbenzoyl)diphenylphosphine oxide, bis(1-(2,4-difluorophenyl)-3-pyrrolyl)titanocene (i.e., photoinitiator 784) or oxybis(ethane-2,1-diyl)bis(2-oxo-2-phenylacetate) (i.e., photoinitiator 754).
[0039] According to some embodiments of the present invention, the photoinitiator is more preferably photoinitiator 819.
[0040] The second aspect of the present invention provides a method for preparing the polyester resin of the first aspect of the present invention, comprising the following steps:
[0041] Under light-proof conditions, the PPF is dissolved in the DEF, then a DMA solution is added, and finally the photoinitiator is added, and the mixture is evenly mixed to obtain the polyester resin.
[0042] A technical solution in the method for preparing polyester resin of the present invention has at least the following beneficial effects:
[0043] This preparation method not only improves the hydrophilicity of the material by introducing DMA into the PPF cross-linked network, but also enhances its bioactivity and interaction with bioactive substances. In addition, the resin is suitable for 3D printing technology based on PμSL, which can manufacture high-precision personalized bone tissue engineering scaffolds and can load bioactive substances to further improve the bone regeneration effect. The simple preparation process and broad application prospects make this technology have great potential in the field of bone tissue engineering.
[0044] The preparation method of the present invention does not require expensive equipment and complicated process control, has undemanding reaction conditions, has readily available raw materials, has low production costs, and is easy to industrialize.
[0045] According to some embodiments of the present invention, the solvent of the DMA solution is preferably N,N-dimethylformamide.
[0046] According to some embodiments of the present invention, the temperature of the mixing process is 80-120°C.
[0047] The third aspect of the present invention provides a biomedical material prepared from the polyester resin of the first aspect of the present invention.
[0048] A technical solution of the present invention in biomedical materials has at least the following beneficial effects:
[0049] The biomedical material provided by the present invention optimizes the hydrophilicity and biological activity of the material by introducing photoreactive dopamine molecules, and significantly enhances its application effect in bone tissue engineering. The material can promote cell adhesion, proliferation and differentiation, support bone regeneration, is suitable for personalized 3D printing technology, and has good biodegradability and mechanical properties, and can provide patients with efficient and accurate treatment. Its simple preparation process and wide application prospects make this material have great potential in the field of biomedicine.
[0050] According to some embodiments of the present invention, the biomedical materials include repair materials, implant materials, drug delivery materials, diagnostic materials, surface treatment materials, biosensor materials, and gene and cell therapy materials.
[0051] Repair materials are used to repair and replace damaged human tissues or organs, and can provide support and promote repair in the damaged area. They include bone tissue engineering materials, soft tissue engineering materials, and joint and cartilage replacement materials. Among them, bone tissue engineering materials such as bone tissue engineering scaffolds, bone replacement materials, etc. are mainly used for the repair and regeneration of bone defects. Soft tissue engineering materials are used to repair damage to soft tissues such as skin, muscles, nerves, and cardiovascular. For example, biodegradable dressings or synthetic skin materials for trauma repair. Joint and cartilage replacement materials are used to repair damaged articular cartilage, and usually use scaffolds made of biomaterials (such as hydroxyapatite, polymer composites, etc.).
[0052] Implantable materials are usually used as artificial substitutes and are implanted in the human body for a long time or permanently to replace or support physiological functions.
[0053] Drug delivery materials are used to accurately deliver active ingredients such as drugs, genes, proteins, etc. to designated locations.
[0054] Diagnostic materials are used in biomedical imaging, in vitro diagnostics, etc. to help medical staff detect and diagnose diseases.
[0055] Surface treatment materials are used to improve the biocompatibility or performance of implant surfaces.
[0056] Biosensing materials and tissue engineering materials combine the principles of biology, materials science, and engineering to prepare artificial biomaterials that can simulate the structure of human tissues and organs.
[0057] Gene and cell therapy materials are used to deliver gene or cell therapy agents to promote disease treatment or tissue repair.
[0058] The fourth aspect of the present invention provides use of the polyester resin of the first aspect of the present invention in 3D printing.
[0059] By applying the polyester resin of the present invention to 3D printing technology, high-precision, personalized bone tissue engineering scaffold manufacturing can be achieved. The beneficial effects of this application include enhancing the biological activity of the scaffold, improving its hydrophilicity, optimizing mechanical properties, improving the therapeutic effect, and being able to simplify the preparation process and reduce costs. The application of 3D printing also makes personalized treatment possible, further improving the accuracy and effect of clinical treatment. Therefore, the application of the polyester resin of the present invention in 3D printing provides a new solution for bone tissue engineering and other medical fields, and has broad clinical application prospects.
[0060] According to some embodiments of the present invention, the 3D printing technology is PμSL technology.
[0061] According to some embodiments of the present invention, no additional sunscreen is required during the 3D printing process. BRIEF DESCRIPTION OF THE DRAWINGS
[0062] Figure 1 This is a schematic diagram of the synthesis process of DMA.
[0063] Figure 2 Schematic diagram of the 3D printing process of unsaturated polyester resin containing photoreactive dopamine.
[0064] Figure 3 Schematic diagram of loading bioactive substances on the surface of 3D printed scaffolds.
[0065] Figure 4 This is the NMR of dopamine hydrochloride and DMA 1 H spectrum.
[0066] Figure 5 This is the NMR of dopamine hydrochloride and DMA 13 C spectrum.
[0067] Figure 6 It is the Fourier transform infrared spectra of dopamine hydrochloride, DMA and photo-crosslinked samples.
[0068] Figure 7 are the test results of gel fraction and swelling ratio of the photo-crosslinked samples.
[0069] Figure 8 It is the water contact angle test result of the photocrosslinked sample.
[0070] Fig. 9 It is the test result of the coefficient of friction of the photo-cross-linked sample surface.
[0071] Fig.10 These are the test results of tensile and compressive mechanical properties of photocrosslinked samples.
[0072] Fig.11It is the cytotoxicity test result of the photo-cross-linked sample.
[0073] Fig.12 This is the test result of the osteogenic differentiation effect of the photocross-linked sample on MC3T3 cells.
[0074] Fig.13 It is the 3D printing “working curve” of unsaturated polyester resin.
[0075] Fig.14 It is a 3D printed bionic structural scaffold prepared from 10% DMA / PPF / DEF unsaturated polyester resin.
[0076] Fig.15 It is a 3D printed bionic structure bracket made of PPF / DEF unsaturated polyester resin. DETAILED DESCRIPTION
[0077] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.
[0078] In the description of the present invention, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.
[0079] Unless otherwise specified, "room temperature" in the present invention means 25±5°C.
[0080] Unless otherwise specified, "about" in the present invention means that the allowable error is within ±2%.
[0081] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.
[0082] Example 1
[0083] A polyester resin containing photoreactive dopamine was prepared by the following method:
[0084] 1) Synthesis of DMA: Figure 1 As shown, 20 g of sodium tetraborate and 8 g of sodium bicarbonate were dissolved in 200 mL of deionized water, and high-purity nitrogen (argon) was bubbled for 20 min, and then 10 g of dopamine hydrochloride (52.73 mmol) was added to the solution.
[0085] If necessary, add 1 M sodium hydroxide to the solution to make the pH value of the system above 8, then dissolve 9.4 mL of methacrylic anhydride (59.3 mmol) in 50 mL of tetrahydrofuran and add it dropwise into the solution, and the system is reacted at room temperature overnight under nitrogen (argon) atmosphere.
[0086] The white precipitate at the bottom of the flask was removed by two centrifugations (the precipitate was washed three times with deionized water), and the reaction mixture was transferred into a separatory funnel and washed twice with 100 mL of ethyl acetate.
[0087] Concentrated hydrochloric acid was added to lower the pH of the solution to below 2, at which time DMA precipitated from the solution. DMA was then extracted with 100 mL of ethyl acetate and allowed to stand for 20 min after shaking. This was repeated three times. The ethyl acetate layers after the three extractions were mixed and dried over anhydrous sodium sulfate. The precipitate was removed by centrifugation twice (the precipitate was washed three times with ethyl acetate), and the volume of the solution was reduced to about 50 mL by rotary evaporation.
[0088] Finally, 450 mL of hexane was added to the solution and stirred vigorously. The resulting suspension was allowed to stand at 4° C. overnight to allow the product to recrystallize from the hexane. The product was vacuum dried (freeze dried) to obtain a gray solid powder.
[0089] 2) Synthesis of PPF: 220 g of DEF and 290.51 g of 1,2-propylene glycol were added into a three-necked flask in sequence, stirred at 150 rpm for 20 min under a nitrogen atmosphere (flow rate: 3 to 5 bubbles per second), then 1.73 g of zinc chloride and 0.28 g of hydroquinone were added, and the mixture was stirred at 100 ° C and 300 rpm for 30 min, then heated to 150 ° C for 7 h, and then cooled to 100 ° C to obtain di(hydroxypropyl) fumarate intermediate.
[0090] Vacuum was applied, and the reaction was carried out at 100°C for 1 hour, then the temperature was raised to 150°C for 4 hours. The product was purified and dried to obtain PPF with a number average molecular weight of 2489 and a weight average molecular weight of 5014.
[0091] 3) Preparation of unsaturated polyester resin DMA / PPF / DEF containing photoreactive dopamine: Under light-proof conditions, 9 g of PPF was dissolved in 9 g of DEF, and then 2 g (10% of the total mass of DMA, PPF and DEF) of DMA was dissolved in 2 mL of N,N-dimethylformamide and added to the mixture. After mixing, 0.2 g (1% of the total mass of DMA, PPF and DEF) of photoinitiator 819 was added to the mixture, and the mixture was kept warm at 100° C. and mixed thoroughly. The obtained unsaturated polyester resin was recorded as 10% DMA / PPF / DEF.
[0092] Example 2
[0093] A polyester resin containing photoreactive dopamine was prepared.
[0094] The difference from Example 1 is that in Example 2, the masses of DMA, PPF and DEF are 1 g, 9.5 g and 9.5 g respectively, 1 g of DMA is dissolved in 1 mL of N,N-dimethylformamide, and the remaining components and preparation process are the same as those of Example 1. The obtained unsaturated polyester resin is recorded as 5% DMA / PPF / DEF.
[0095] Example 3
[0096] A polyester resin containing photoreactive dopamine was prepared.
[0097] The difference from Example 1 is that in Example 3, the masses of DMA, PPF and DEF are 3 g, 8.5 g and 8.5 g respectively, 3 g DMA is dissolved in 3 mL N,N-dimethylformamide, and the remaining components and preparation process are the same as those in Example 1. The obtained unsaturated polyester resin is recorded as 15% DMA / PPF / DEF.
[0098] Comparative Example 1
[0099] A polyester resin was prepared.
[0100] The difference from Example 1 is that Comparative Example 1 only contains PPF, DEF and photoinitiator 819, the mass of PPF and DEF is 10 g each, the mass of photoinitiator 819 is 0.2 g (1% of the total mass of PPF and DEF), and the preparation process is similar to that of Example 1. The obtained unsaturated polyester resin is recorded as PPF / DEF.
[0101] Example 4
[0102] The unsaturated polyester resins in Examples 1-3 were taken respectively, and the uniform mixture was transferred to a 0.5 mm thick silicone mold, which was clamped by two glass plates (2.1 mm thick) at the top and bottom, and then placed under ultraviolet light (365 nm) for 40 min (7 cm from the UV lamp head). The cross-linked slices were taken out after cooling to room temperature, and then samples of different sizes and shapes were cut from the slices and dried. Except for the samples used to determine the gel fraction and swelling rate, they were immersed in acetone for two days to remove the uncross-linked parts, and then vacuum dried for experimental characterization. The samples used to determine the gel fraction and swelling rate were directly used for experimental characterization without acetone treatment.
[0103] Comparative Example 2
[0104] The difference from Example 4 is that in Comparative Example 2, the PPF / DEF unsaturated polyester resin in Comparative Example 1 is used instead of the resin in Example 4, and the preparation process is the same as that of Example 4.
[0105] Example 5
[0106] Printing of three-dimensional porous scaffolds: Take the unsaturated polyester resin in Example 1 and perform photo-crosslinking 3D printing (schematic diagram as shown in FIG. Figure 2 shown).
[0107] The steps include:
[0108] 1) Model design: A 3D stent model with spherical holes was constructed in Abaqus software. The overall shape of the stent was cylindrical with a diameter of 3 mm and a height of 4 mm.
[0109] 2) Model slicing: export the 3D stent model into binary STL format, import it into Creationworkshop slicing software and cut it into 2D projection graphics;
[0110] 3) The image information was input into the computer for layer-by-layer photo-crosslinking 3D printing. The printer model was nanoArch P140 (BMF Precision Tech Inc.), the printing layer thickness was 20 μm per layer, the UV wavelength was 405 nm, the exposure time for each layer was 30 s, and the UV intensity was 6.5 mW / cm 2 , the printing temperature is controlled at 50℃;
[0111] 4) Carefully remove the scaffold from the printing platform with a blade, and remove excess resin inside the pores by centrifugation at a speed of 5000 r / min for 5 min;
[0112] 5) The scaffold was placed in a curing box and cured for 1.5 hours at a wavelength of 405 nm to obtain a three-dimensional porous scaffold.
[0113] Comparative Example 3
[0114] The difference from Example 5 is that in Comparative Example 3, the PPF / DEF unsaturated polyester resin in Comparative Example 1 is used instead of the resin in Example 5, the exposure time of each layer is 2.5 s, and the UV light intensity is 35 mW / cm 2 The rest of the preparation process is the same as in Example 5.
[0115] Example 6
[0116] The three-dimensional porous scaffold obtained in Example 5 is further loaded with bioactive substances (such as BMP-2) on the surface of the scaffold to promote bone regeneration, as shown in the schematic diagram Figure 3 shown.
[0117] The steps include:
[0118] Different masses of BMP-2 protein were dissolved in phosphate buffer solution to form BMP-2 protein solutions of different concentrations (1, 5 and 10 μg / mL), and then the scaffolds were immersed in them and incubated on a shaker at 4°C for 24 h. The scaffolds were washed three times with phosphate buffer solution to remove unbound BMP-2 protein, and finally the surface functionalized scaffolds were freeze-dried.
[0119] Effect Example
[0120] 13 mg of DMA synthesized in Example 1 was dissolved in 0.55 mL of deuterated dimethyl sulfoxide, with tetramethylsilane as the internal standard, and NMR was performed at room temperature. 1 H spectrum and 13 The results of C spectrum determination are as follows Figure 4 , Figure 5 shown.
[0121] The chemical shifts of all spectral peaks can be well attributed to the corresponding protons in the compound structures. 1 In the H spectrum, the resonance signal with a chemical shift of 1.84 ppm is attributed to the methyl proton, and the resonance signals with chemical shifts of 5.29 and 5.61 ppm are attributed to the olefin protons. Compared with the spectrum of dopamine hydrochloride, the appearance of absorption peaks at these two positions indicates the success of the methacrylation reaction. 13 In the C spectrum, the resonance signal with a chemical shift of 18.52 ppm is attributed to the methyl carbon atom, the resonance signals with chemical shifts of 118.63 and 139.99 ppm are attributed to the olefinic carbon atom, and the resonance signal with a chemical shift of 167.21 ppm is attributed to the carbonyl carbon atom. Compared with the spectrum of dopamine hydrochloride, the appearance of absorption peaks at these positions indicates the success of the methacrylation reaction.
[0122] The DMA synthesized in Example 1 and the photo-crosslinked samples obtained in Example 4 and Comparative Example 2 were subjected to Fourier transform infrared spectroscopy analysis and characterization. The DMA powder and potassium bromide were ground and pressed into tablets using the transmission mode, and the photo-crosslinked samples were subjected to the attenuated total reflection mode. The results are as follows: Figure 6 shown.
[0123] In the infrared spectrum of DMA, 1649 cm -1 and 1718cm -1 The absorption peaks at the two positions are caused by the stretching vibrations of the carbon-carbon double bond and the carbon-oxygen double bond, respectively. Comparing with the spectrum of dopamine hydrochloride, the appearance of the absorption peaks at these two positions indicates the success of the methacrylation reaction.
[0124] The photo-crosslinked samples obtained in Example 4 and Comparative Example 2 were taken to measure the gel fraction and swelling ratio.
[0125] The sample was weighed after drying, recorded as W0. After the sample was immersed in dichloromethane for two days to reach swelling equilibrium, the sample was taken out and the surface liquid was quickly absorbed with filter paper or cloth, and then weighed immediately, recorded as W s The sample was then vacuum dried and weighed, recorded as W d , the sample gel fraction is given by the formula W d / W0 is calculated, and the swelling rate in dichloromethane is calculated by the formula (W s -W d ) / W d Calculated.
[0126] Then soak the sample in phosphate buffer solution for two days, take out the sample and quickly absorb the surface liquid with filter paper or cloth, then weigh it immediately, record it as W s’ The swelling rate of the sample in phosphate buffer solution is given by the formula (W s’ -W d ) / W d The gel fraction reflects the efficiency of polymer chain cross-linking and determines the integrity of the cross-linked product.
[0127] The results are as follows Figure 7 As shown, the gel fraction of the cross-linked network prepared by PPF / DEF is close to 0.9. With the increase of DMA content in the cross-linked network, the gel fraction decreases, while the swelling rate in dichloromethane gradually increases. All samples hardly swell in phosphate buffer solution.
[0128] The photo-crosslinked samples obtained in Example 4 and Comparative Example 2 were taken for surface water contact angle measurement. 1 μL of ultrapure water was dropped onto the sample surface and the water contact angle was measured by the sessile drop method after standing for 30 seconds. The results are shown in FIG. Figure 8As shown, as the DMA content in the cross-linked network increased from 0% to 15%, the water contact angle decreased from 71.7° to 55.4°, which indicates that the hydrophilicity of the material surface is improved due to the presence of dopamine molecules.
[0129] Take the photocross-linked samples obtained in Example 4 and Comparative Example 2, fix them on the flat clamp of the rotational rheometer, fill the space between the sample surface and the other clamp with water, rotate the clamp at a constant speed of 50 rpm, increase the normal force load linearly from 0 N to 3 N over time, record the torque T and the normal force W, and calculate the friction force f by the formula f=4T / 3r, where r is the sample radius. Finally, the friction coefficient μ is calculated by the formula μ=f / W.
[0130] like Fig. 9 As shown in the figure, the results show that due to the introduction of dopamine molecules into the cross-linked network, the friction coefficient of the material surface is significantly reduced compared with PPF / DEF, but with the increase of DMA content, the friction coefficient increases again, which may be caused by the adhesion of catechol groups. This further illustrates that dopamine molecules can be used to improve the surface properties and interface interactions of materials.
[0131] The dumbbell-shaped splines and solid cylindrical photo-crosslinked samples obtained in Example 4 and Comparative Example 2 were respectively subjected to mechanical property tests, including uniaxial tension and compression, using a constant deformation rate of 0.25 mm / min to characterize the tensile / compression Young's modulus, tensile strength and fracture strain. The results are as follows: Fig.10 shown.
[0132] With the increase of DMA content in the cross-linked network, both the tensile and compressive Young's moduli decreased significantly, while the tensile strength and break strain showed an upward trend.
[0133] The photo-crosslinked samples obtained in Example 4 and Comparative Example 2 were used for cytotoxicity testing. MC3T3 cells were exposed to sterile disc samples through culture medium to test the cytotoxicity of the material extract. The fused MC3T3 cells were digested and prepared into a cell suspension at 15,000 cells / cm 2 The cells were inoculated at a density of 1 mL in a 24-well culture plate. After 4 hours, the sterile photocrosslinked disc samples were placed in the Transwell chambers, and then the Transwell chambers and samples were placed in the 24-well plate, and 0.3 mL of culture medium was added to the Transwell chambers. The positive control used a group with the same cell density but no material, and the negative control used a blank well. The cells were counted using a cell counting kit at 1, 2, 4, and 7 days, and the absorbance was measured at a wavelength of 450 nm using an enzyme reader. The ratio of the absorbance value of the experimental group to the absorbance value of the positive control group indicated the cell survival rate.
[0134] like Fig.11As shown, the results showed that the cell survival rate of each experimental group was above 95%, indicating that no toxic molecules were leached from the samples and all samples had good compatibility with MC3T3 cells.
[0135] The photo-crosslinked samples obtained in Example 4 and Comparative Example 2 were sterilized and used to culture MC3T3 cells. The fused MC3T3 cells were digested to prepare a cell suspension and cultured at 15,000 cells / cm 2 The density of cells was inoculated on the surface of the photo-crosslinked sample, and the cells were cultured in MEMα medium for one day and then replaced with osteogenic differentiation medium for seven days. Fresh differentiation medium was replaced every three days, and then the degree of osteogenic differentiation of cells was evaluated. On the one hand, alkaline phosphatase is one of the osteogenic-specific matrix proteins, and alkaline phosphatase activity is the most widely recognized marker of osteoblast activity. MC3T3 cells cultured on the surface of the material were fixed with 4% paraformaldehyde at room temperature for 30 minutes, and then the BCIP / NBT alkaline phosphatase colorimetric kit was used to prepare the staining working solution. The cells were incubated with the working solution at room temperature in the dark for 50 minutes, the staining working solution was discarded, and the cells were washed 1 to 2 times with phosphate buffer solution and observed under a microscope and photographed. On the other hand, the Alizarin Red staining solution can stain a small amount of calcium deposits, which is suitable for the staining of calcium salt tissue in the osteogenic differentiation of cells. The MC3T3 cells cultured on the surface of the material were fixed with 4% paraformaldehyde at room temperature for 30 minutes, 2 mL of Alizarin Red working solution was added to each well, and the cells were stained at room temperature for 2 hours. The Alizarin Red staining solution was aspirated and the cells were gently washed 2 to 3 times with phosphate buffer solution to fully wash away the excess staining solution, and then observed and photographed under a microscope.
[0136] The results are as follows Fig.12 As shown in the figure, in alkaline phosphatase staining, compared with the PPF / DEF group, the number of stained cells on the photo-crosslinked samples containing DMA was significantly larger and the color was darker, among which the osteogenic differentiation effect of the 10% DMA / PPF / DEF group was the best; in Alizarin red staining, the cells in the 10% DMA / PPF / DEF and 15% DMA / PPF / DEF groups were darker, and the 15% DMA / PPF / DEF group showed the presence of calcium nodules. The above results show that photo-crosslinked samples containing DMA can significantly promote the osteogenic differentiation of MC3T3 cells.
[0137] The unsaturated polyester resins in Example 1 and Comparative Example 1 were subjected to photo-crosslinking 3D printing under UV light of different light intensities at the same time, and then the actual cured layer thickness was measured under a microscope to obtain the relationship between the cured layer thickness and the initial UV energy of the resin surface layer. According to formula C d =D p ·(lnE max -lnE c ) is linearly fitted to obtain the "working curve" of unsaturated polyester resin, where C dis the curing depth, D p is the penetration depth, E max is the maximum exposure energy of the resin surface, E c is the critical exposure energy.
[0138] The results are as follows Fig.13 As shown, D can be calculated from the slope and intercept of the fitting line. p With E c , 10% DMA / PPF / DEF resin has higher D than PPF / DEF resin p With E c In order to meet the printing accuracy requirements, the UV light intensity is 6.5mW / cm 2 , the bionic three-dimensional structure was prepared by 3D printing of 10% DMA / PPF / DEF resin under the condition of 30s exposure time, and the corresponding curing depth was 96.5μm.
[0139] The three-dimensional porous scaffolds obtained in Example 5 and Comparative Example 3 were photographed and characterized by SEM. The results are as follows: Fig.14 , Fig.15 shown.
[0140] As can be seen from the figure, the 3D printed bionic scaffold prepared by 10% DMA / PPF / DEF unsaturated polyester resin has a complete structure, interconnected pores, and ideal printing accuracy, indicating that the new unsaturated polyester resin containing photoreactive dopamine in this invention can be applied to PμSL-based 3D printing technology.
[0141] In some embodiments of the present invention, a biomedical material is also provided, which is prepared from the polyester resin of the present invention.
[0142] Since dopamine molecules are introduced into the polyester resin, the surface of the prepared material is modified by dopamine, which significantly improves the hydrophilicity of the surface. This modification can effectively improve the contact between the material and the surrounding biological tissues and enhance its biocompatibility. Materials with good biocompatibility can reduce immune rejection and adverse reactions and provide a good microenvironment for tissue repair and regeneration.
[0143] Dopamine and its derivatives (such as DMA) can interact with the extracellular matrix and related proteins (such as BMP-2) through their active functional groups. This enables the biomedical material to promote the adhesion, proliferation and differentiation of osteoblasts and other related cells, especially in bone tissue engineering, and can effectively promote bone regeneration and repair.
[0144] The catechol group structure in the dopamine molecule has excellent adhesion properties and biological activity. It can adsorb bioactive substances such as growth factors and cytokines, further enhance its biological effects in the body, and promote tissue repair and regeneration.
[0145] Furthermore, the polyester resin used in this biomedical material is suitable for PμSL-based 3D printing technology. Through PμSL technology, complex three-dimensional structure scaffolds can be accurately manufactured to meet the personalized treatment needs of different patients. 3D printing allows the scaffold to be customized according to the patient's specific bone defect area, ensuring higher adaptability and treatment effect.
[0146] In addition, the high resolution and high precision of 3D printing ensure the structural integrity and accuracy of the scaffold, which helps the scaffold better integrate with bone tissue in the body and provide long-term support.
[0147] It can be understood that the biomedical material of the present invention can not only provide an ideal growth environment for osteoblasts, but also load bioactive substances (such as BMP-2, etc.) to further promote bone regeneration. The loading of bioactive substances can effectively promote the repair process of bone tissue and improve the healing speed and quality of bone defect areas.
[0148] Through the modification of dopamine and its derivatives, the surface of the scaffold has better cell adsorption performance and growth factor binding ability, which enhances the function of the bone tissue engineering scaffold and further promotes osteogenic differentiation and mineralization.
[0149] PPF itself is biodegradable, which allows the biomedical materials prepared from it to gradually degrade in the body, avoiding the negative effects that may be caused by long-term implantation. The degradation rate and mechanical properties of the material can be achieved by adjusting the resin formula and cross-linking degree, thereby achieving coordination with tissue growth.
[0150] The mechanical properties of the material can be adjusted according to actual needs to ensure its support role during bone regeneration and avoid premature degradation that leads to instability of the bone defect site.
[0151] In addition, the method for preparing the biomedical material is simple and efficient, using a dissolution and mixing process under light-proof conditions, and can prepare a resin with excellent performance in a relatively short time. Compared with traditional biomedical material preparation methods, this process has higher efficiency and lower cost, and is suitable for large-scale production and clinical applications.
[0152] This biomedical material can not only be used in bone tissue engineering, but also be extended to other soft tissue repair, tissue engineering, drug delivery systems, etc. Its good biocompatibility, degradability and bioactivity make it have broad application prospects in regenerative medicine.
[0153] Therefore, the biomedical material provided by the present invention optimizes the hydrophilicity and biological activity of the material by introducing photoreactive dopamine molecules, and significantly improves its application effect in bone tissue engineering. The material can promote cell adhesion, proliferation and differentiation, support bone regeneration, is suitable for personalized 3D printing technology, and has good biodegradability and mechanical properties, and can provide patients with efficient and accurate treatment. Its simple preparation process and wide application prospects make this material have great potential in the field of biomedicine.
[0154] In some embodiments of the present invention, there is provided application of the polyester resin according to the first aspect of the present invention in 3D printing.
[0155] It should be noted that the polyester resin of the present invention can be effectively applied to the high-precision 3D printing technology PμSL. PμSL technology has extremely high resolution and precision, and can produce complex three-dimensional structures at the micron level. Through this technology, delicate and complex bone tissue engineering scaffolds can be accurately manufactured to meet personalized treatment needs, and are particularly suitable for customized design and manufacturing of specific bone defect areas of patients.
[0156] The resin curing process is not restricted by traditional manufacturing processes and can design and print scaffold structures of any complex shape, ensuring that the scaffold perfectly matches the bone defect site and improving the treatment effect.
[0157] It is understandable that by adjusting the resin formula and printing parameters (such as exposure intensity, exposure time, etc.), the cross-linking degree, mechanical properties and degradation rate of the material can be adjusted to meet the needs of different bone defect repairs. This makes the resin more applicable in 3D printing applications and can be customized to meet the different needs of different patients.
[0158] It can also be understood that by precisely controlling the structure of the material, the mechanical properties of the scaffold can be adapted to the biological tissue, ensuring that the scaffold provides adequate support to the surrounding tissue during bone regeneration while avoiding premature degradation or insufficient strength.
[0159] The resin can retain the hydrophilicity and bioactivity brought by DMA during the printing process. Dopamine molecules can interact with the extracellular matrix and bioactive substances (such as BMP-2) through their active functional groups to enhance the adhesion, proliferation and differentiation ability of the scaffold surface and cells. This can effectively promote the proliferation and mineralization of osteoblasts and help repair and regenerate bone defects.
[0160] The resin surface can effectively adsorb and load various bioactive substances (such as growth factors, cytokines, etc.), further promoting the process of bone regeneration.
[0161] It can be understood that the use of the polyester resin of the present invention for 3D printing can efficiently and quickly prepare customized bone tissue scaffolds. Compared with traditional manufacturing methods, 3D printing can significantly reduce production time and labor costs. Especially in personalized treatment, 3D printing can accurately manufacture suitable scaffolds according to the specific bone defect conditions of the patient, avoiding the adaptation problems of prefabricated prostheses used in traditional surgery.
[0162] Furthermore, the preparation process of the resin is simple, using a dissolution and mixing process, and is well compatible with 3D printing technology, enabling more efficient production, and is particularly suitable for large-scale production and clinical applications.
[0163] It is understandable that the resin is derived from PPF and has good biodegradability. The printed bone tissue scaffold can gradually degrade in the body, avoiding complications or immune rejection that may be caused by long-term implantation.
[0164] By adjusting the different components of the resin formula, the degradation rate of the scaffold can be controlled to meet the needs of different bone defect repairs. The degradation of the material is coordinated with the rate of new bone growth, thus achieving an ideal tissue repair process.
[0165] 3D printing technology can customize personalized bone tissue engineering scaffolds according to the specific needs of patients. The shape, size, depth, etc. of bone defects in different patients vary, and prostheses made using traditional methods often cannot perfectly match. 3D printing can provide personalized solutions, improve the success rate of surgery, and make treatment more precise.
[0166] Wide range of clinical applications: This resin can be widely used in clinical fields such as bone defect repair, bone transplantation, spinal surgery, joint repair, etc., and has broad market prospects and application potential.
[0167] In addition to bone tissue engineering, the polyester resin of the present invention can also be widely used in other medical fields, such as soft tissue repair, drug delivery system, nerve regeneration, etc. With the support of 3D printing technology, it can meet a variety of medical needs and provide more innovative solutions.
[0168] Loading of bioactive substances: The surface of the stent can effectively load bioactive substances, such as growth factors, proteins, gene drugs, etc., further expanding its application potential in regenerative medicine and personalized medicine.
[0169] Therefore, by applying the polyester resin of the present invention to 3D printing technology, high-precision, personalized bone tissue engineering scaffold manufacturing can be achieved. The beneficial effects of this application include enhancing the biological activity of the scaffold, improving its hydrophilicity, optimizing mechanical properties, improving the therapeutic effect, and being able to simplify the preparation process and reduce costs. The application of 3D printing also makes personalized treatment possible, further improving the accuracy and effect of clinical treatment. Therefore, the application of the polyester resin of the present invention in 3D printing provides a new solution for bone tissue engineering and other medical fields, and has broad clinical application prospects.
[0170] The present invention has been described in detail above in conjunction with the embodiments, but the present invention is not limited to the above embodiments, and various changes can be made within the knowledge scope of ordinary technicians in the relevant technical field without departing from the purpose of the present invention.
Claims
1. A polyester resin containing photoreactive dopamine, characterized in that: The preparation raw materials include dopamine methacrylamide, polypropylene glycol fumarate, diethyl fumarate and a photoinitiator.
2. The polyester resin according to claim 1, characterized in that By weight, the raw materials for preparation include: Dopamine methacrylamide: 5-15 parts, Polypropylene fumarate: 42.5-47.5 parts, Diethyl fumarate: 42.5-47.5 parts, Photoinitiator: 0.45 to 3.3 parts.
3. The polyester resin according to claim 1 or 2, characterized in that The preparation method of dopamine methacrylamide comprises the following steps: dissolving sodium tetraborate, sodium bicarbonate and dopamine hydrochloride in water, adjusting the pH of the system, then adding methacrylic anhydride dropwise, washing, extracting, drying and then recrystallizing the product.
4. The polyester resin according to claim 1 or 2, characterized in that The preparation method of polypropylene fumarate comprises the following steps: mixing diethyl fumarate, 1,2-propylene glycol, a catalyst and an inhibitor, performing a first step reaction to obtain a di(hydroxypropyl) fumarate intermediate, and then performing a second step ester exchange reaction to obtain the polypropylene fumarate after polycondensation.
5. The polyester resin according to claim 1 or 2, characterized in that The photoinitiator includes at least one of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, (2,4,6-trimethylbenzoyl)diphenylphosphine oxide, bis(1-(2,4-difluorophenyl)-3-pyrrolyl)titanocene or oxybis(ethane-2,1-diyl)bis(2-oxo-2-phenylacetate).
6. A method for preparing a polyester resin containing photoreactive dopamine as claimed in any one of claims 1 to 5, characterized in that: The method comprises the following steps: dissolving the polypropylene fumarate in the diethyl fumarate under light-proof conditions, then adding a dopamine methacrylamide solution, and finally adding the photoinitiator, and mixing them evenly to obtain the polyester resin.
7. The method according to claim 6, characterized in that The temperature of the mixing process is 80-120°C.
8. A biomedical material, characterized in that: The method is prepared from the polyester resin containing photoreactive dopamine according to any one of claims 1 to 5.
9. The biomedical material according to claim 8, characterized in that: The biomedical materials include repair materials, implant materials, drug delivery materials, diagnostic materials, surface treatment materials, biosensor materials, and gene and cell therapy materials.
10. Use of the polyester resin containing photoreactive dopamine according to any one of claims 1 to 5 in 3D printing.
Citation Information
Patent Citations
Injectable hydrogel microsphere for treating orthopedic diseases as well as preparation method and application thereof
CN112618571A
Solvent free resorbable resin for 3D printing
WO2025085293A1